Rosetta lander Philae: Flight Dynamics analyses for landing site selection and post-landing operations. (August 2016) - Jurado, Eric; Martin, Thierry; Canalias, Elisabet; Blazquez, Alejandro; Garmier, Romain; Ceolin, Thierry; Gaudon, Philippe; Delmas, Cedric; Biele, Jens; Ulamec, Stephan; Remetean, Emile; Torres, Alex; et al.
Abstract: On the 12th of November 2014, The Rosetta Lander Philae became the first spacecraft to softly land on a comet nucleus. Due to the double failure of the cold gas hold-down thruster and the anchoring harpoons that should have fixed Philae to the surface, it spent approximately two hours bouncing over the comet surface to finally come at rest one km away from its target site. Nevertheless it was operated during the 57 h of its First Science Sequence. The FSS, performed with the two batteries, should have been followed by the Long Term Science Sequence but Philae was in a place not well illuminated and fell into hibernation. Yet, thanks to reducing distance to the Sun and to seasonal effect, it woke up at end of April and on 13th of June it contacted Rosetta again. To achieve this successful landing, an intense preparation work had been carried out mainly between August and November 2014 to select the targeted landing site and define the final landing trajectory. After the landing, the data collected during on-comet operations have been used to assess the final position and orientation of Philae, and to prepare the wake-up. This paper addresses the Flight Dynamics studies done in the scope of this landing preparation from Lander side, in close cooperation with the team at ESA, responsible for Rosetta, as well as for the reconstruction of the bouncing trajectory and orientation of the Lander after touchdown. Highlights: Philae landing site selection process took place from July to October 2014. Flight Dynamics studies helped lander team to choose landing site. Despite unexpected bouncing, Philae carried out its main mission after landing. FD team helped reconstructing lander position and attitude. Bouncing trajectory from first touchdown to final rest was also reconstructed.